Meningkatkan Pemahaman dan Edukasi Mengenai Gejala Hipertensi pada Masyarakat di Desa Cinta Rakyat Kecamatan Percut Sei Tuan Kabupaten Deli Serdang Tahun 2023 - Lubis, Tiffani Tantina; Batubara, Saiful (Health Community Service, 2024)
Thematic Real Work Lectures (KKN-Thematic) have been held in Cinta Rakyat Village for 21 days from September 14 to 3, 2023. Cinta Rakyat Village is one of the villages in Percut Sei Tuan District, Deli Serdang Regency, North Sumatra Province, Indonesia. Various Thematic KKN programs have been implemented. Thematic KKN activities that have been carried out begin with village observation, program planning, program consultation to villagers, villagers and DPL. Thematic KKN activities carried out include the preparation and implementation stages of the program. The result achieved from the implementation of the group's program is to provide process changes to improve the literacy of the residents of Cinta Rakyat Village in the digital era. Broadly speaking, the programs that have been prepared can run well and can provide benefits for the progress of villagers and to add useful experiences for the future. The Thematic KKN program apart from being a forum for training and learning for students, is also an effort by the Islamic University of North Sumatra to contribute to transforming educational values to the village. The hope is not only the transfer of knowledge provided by students, but also the transfer of value. The existence of UISU Thematic KKN-Thematic students 2023 is expected to make changes as an effort to advance Indonesian education.